2023
DOI: 10.1136/bmjopen-2022-068849
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidities on hospitalised Syrian patients with COVID-19: a retrospective study

Abstract: ObjectivesThis study aims to compare the clinical manifestations, laboratory findings, outcomes and overall survival time of patients with COVID-19 with and without comorbidities.DesignRetrospective design.SettingThis study was undertaken at two hospitals in Damascus.ParticipantsA total of 515 Syrian patients met the inclusion criterion, laboratory-confirmed COVID-19 infection following the Centers for Disease Control and Prevention. Exclusion criteria were suspected and probable cases that were not confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…These findings reinforce previous studies linking these comorbidities to adverse outcomes of COVID-19 as independent predictors of mortality (Imam et al, 2020;Piskač Živković et al, 2022;Ssentongo et al, 2020). Studies in Syria (Najjar et al, 2023), Egypt (Albadawy et al, 2021), and India (Saurabh ) reported lower survival rates in COVID-19 patients with comorbidities. The study showed that COVID-19 patients with cardiovascular system problems were associated with survival rates before and after adjusting for respondent characteristics.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings reinforce previous studies linking these comorbidities to adverse outcomes of COVID-19 as independent predictors of mortality (Imam et al, 2020;Piskač Živković et al, 2022;Ssentongo et al, 2020). Studies in Syria (Najjar et al, 2023), Egypt (Albadawy et al, 2021), and India (Saurabh ) reported lower survival rates in COVID-19 patients with comorbidities. The study showed that COVID-19 patients with cardiovascular system problems were associated with survival rates before and after adjusting for respondent characteristics.…”
Section: Discussionsupporting
confidence: 89%
“…DM is also correlated with glycemic instability and impaired immune response, which coincides with obesity and heart disease (Kandil et al, 2021), thereby leading to lung dysfunction, such as decreased lung volume (Yan et al, 2020). Typical DM complications such as cardiovascular disease and chronic obstructive pulmonary disease, especially when accompanied by other comorbidities, significantly increase the risk of death in COVID-19 patients (Lim et al, 2021;Najjar et al, 2023). Bello-Chavolla et al supported this by noting that DM was associated with a threefold increased risk of death from COVID-19 after adjusting for age, sex, and comorbidities (Bello-Chavolla et al, 2020).…”
Section: Discussionmentioning
confidence: 99%